TAFSIR ILMU TABYIN: Kemahaluasan Khazanah Ilmu Pengetahuan Islam - mega; Achmad Ainur Ridho (STQINIS, 2024)
Al-Quran al-Karim as the holy book of Muslims is the first and main source of information and inspiration (al-maraji' al-Ula wa al-Awla). However, to be able to get this information and inspiration, it is not as easy as studying the series of letters with their harakat decoration. There needs to be a set of tools that can be used accurately. This activity is called interpretation; efforts to understand the meaning, law and wisdom of the Koran. Such activities are carried out with various approaches complete with styles. One of them is the scientific approach which has become known as Ilmi Tafsir. He is relatively young. Even though the seeds are relatively old. Precisely around the 19th century AD because at that time, Muslims experienced an inferiority complex due to advances in Western science and technology. Meanwhile, Muslims are in the opposite condition. In fact, long before that, when Islam entered Europe, Muslims were the masters of everything, especially science. To restore a pulse that had been dead for a long time, most Islamic figures and scientists began to seriously examine scientific texts in the Koran. This is the basis for the emergence of Tafsir Ilmi. So that at the climax point it can be produced that the Koran contains everything, including scientific things. Even the Koran precedes science. This turning point is what Muslims all over the world really need to understand. Scientific Tafsir is the right solution in an effort to rediscover the vastness of the treasures of knowledge in Islam, as stated in its holy book, the Al-Quran. Keywords: Scientific Tafsir, European Islam, Ummatan Wasathan. Al-Quran al-Karim as the holy book of Muslims is the first and main source of information and inspiration (al-maraji' al-Ula wa al-Awla). However, to be able to get this information and inspiration, it is not as easy as studying the series of letters with their harakat decoration. There needs to be a set of tools that can be used accurately. This activity is called interpretation; efforts to understand the meaning, law and wisdom of the Koran. Such activities are carried out with various approaches complete with styles. One of them is the scientific approach which has become known as Ilmi Tafsir. He is relatively young. Even though the seeds are relatively old. Precisely around the 19th century AD because at that time, Muslims experienced an inferiority complex due to advances in Western science and technology. Meanwhile, Muslims are in the opposite condition. In fact, long before that, when Islam entered Europe, Muslims were the masters of everything, especially science. To restore a pulse that had been dead for a long time, most Islamic figures and scientists began to seriously examine scientific texts in the Koran. This is the basis for the emergence of Tafsir Ilmi. So that at the climax point it can be produced that the Koran contains everything, including scientific things. Even the Koran precedes science. This turning point is what Muslims all over the world really need to understand. Scientific Tafsir is the right solution in an effort to rediscover the vastness of the treasures of knowledge in Islam, as stated in its holy book, the Al-Quran. Keywords: Scientific Tafsir, European Islam, Ummatan Wasathan